Soluble TREM2 drives earliest amyloid‐related p‐tau increase in Alzheimer's disease but attenuates neurodegeneration in advanced disease. (20th December 2022) - Biel, Davina; Ewers, Michael; Suárez‐Calvet, Marc; Hager, Paul; Rubinski, Anna; Dewenter, Anna; Steward, Anna; Roemer, Sebastian Niclas; Haass, Christian; Brendel, Matthias; Franzmeier, Nicolai
Abstract: Background: Alzheimer's disease (AD) is characterized by Aβ and tau accumulation, microglial activation, metabolic brain changes, neurodegeneration, and cognitive decline. Studies found both detrimental and protective effects of microglial activation on AD progression, hence neuroinflammation may be a double‐edged sword in AD, which is critical for clinical trials aiming to modulate microglial activation. Here, we used CSF sTREM2 as a proxy of microglial activation to investigate disease stage‐dependent drivers of microglial activation in AD and its associations with the development of tau, metabolic brain changes, and neurodegeneration. Methods: We included 271 ADNI participants, including cognitively normal (n=71) and mild cognitively impaired (n=200) participants with available CSF Aβ1‐42, p‐tau181, sTREM2, as well as amyloid‐PET and FDG‐PET. To determine disease stage, we stratified patients into Aβ CSF+/PET‐ (early Aβ‐accumulators, n=70) and Aβ CSF+/PET+ (late Aβ‐accumulators, n=201). A subset of 21/75 early/late Aβ‐accumulators had available longitudinal p‐tau181 and sTREM2 assessments, based on which we calculated annual sTREM2 and p‐tau181 change rates. Using linear models and mediation analyses we tested disease stage‐specific associations between amyloid‐PET (centiloid), p‐tau181 and sTREM2, and between sTREM2 and metabolic brain changes (FDG‐PET) or neurodegeneration (grey matter volume), controlling for age, sex, education, and diagnosis. Results: We found that higher centiloid was associated with cross‐sectional and longitudinal increases in p‐tau181 and sTREM2 in early Aβ‐accumulators, while in late Aβ‐accumulators, only a cross‐sectional association between centiloid and p‐tau181 was observed (Fig.1A+B ). In early Aβ‐accumulators, sTREM2 fully mediated the association between centiloid and p‐tau181 (55% mediation) as well as longitudinal p‐tau181 increase (71% mediation) (Fig.1C+D ). Higher sTREM2 was associated with higher FDG‐PET in early Aβ‐accumulators but with lower FDG‐PET in late Aβ‐accumulators (Fig.2A+B ), in line with our previous findings that activated microglia consume glucose. In exploratory analyses, sTREM2 attenuated effects of higher p‐tau181 on hippocampal atrophy in late Aβ‐accumulators (n=155, T=2.215, p=0.031). Conclusion: Earliest Aβ accumulation is associated with elevated sTREM2‐related microglial activation ensuing increases in p‐tau181 and glucose metabolism, whereas higher microglial activation in late Aβ‐accumulators attenuates hippocampal atrophy. Our findings have clinical implications as they suggest that targeting enhancement of microglial activation may have opposing effects on disease progression, depending on disease stage.